Associação do receptor toll-like 2 com o estado pró-inflamatório do diabetes tipo 1 - Ururahy, Marcela Abbott Galvão (2009)
Inflammation has been pointed out as an important factor in development of chronic diseases, as diabetes. Hyperglycemia condition would be responsible by toll-like receptors, TLR2 and TLR4, and, consequently by local and systemic inflammation induction. Thus, the objective of present study was to evaluate type 1 Diabetes mellitus (T1DM) pro-inflammatory state through mRNA expression of TLRs 2 and 4 and proinflammatory cytokines IL-1β, IL-6 and TNF-α correlating to diabetic nephropathy. In order to achieve this objective, 76 T1DM patients and 100 normoglycemic (NG) subjects aged between 6 and 20 years were evaluated. T1DM subjects were evaluated as a total group DM1, and considering glycemic control (good glycemic control DM1G, and poor glycemic control DM1P) and considering time of diagnosis (before achieving 5 years of diagnosis DM1< 5yrs, and after achieving 5 years of diagnosis DM1 <5yrs). Metabolic control was evaluated by glucose and glycated hemoglobin concentrations; to assess renal function serum urea, creatinine, albumin, total protein and urinary albumin-to-creatinine ratio were determined and to evaluate hepatic function, AST and ALT serum activities were measured. Pro-inflammatory status was assessed by mRNA expression of TLRs 2 and 4 and the inflammatory cytokines IL-1β, IL-6 and TNF-α. Except for DM1G group (18.4%), DM1NC patients (81.6%) showed a poor glycemic control, with glycated hemoglobin (11,2%) and serum glucose (225,5 md/dL) concentrations significantly increased in relation to NG group (glucose: 76,5mg/dL and glycated hemoglobin: 6,9%). Significantly enhanced values of urea (20%) and ACR (20,8%) and diminished concentrations of albumin (5,7%) and total protein (13,6%) were found in T1DM patients, mainly associated to a poor glycemic control (DM1P increased values of urea: 20% and ACR:49%, and diminished of albumin: 13,6% and total protein:13,6%) and longer disease duration (DM1 <5yrs - increased values of urea: 20% and ACR:20,8%, and diminished of albumin: 14,3% and total protein:13,6%). As regarding pro-inflammatory status evaluation, significantly increased mRNA expressions were presented for TLR2 (37,5%), IL-1β (43%), IL-6 (44,4%) and TNF-α (15,6%) in T1DM patients in comparison to NG, mainly associated to DM1P (poor glycemic control TLR2: 82%, IL-1β: 36,8% increase) and DM1 <5yrs (longer time of diagnosis TLR2: 85,4%, IL-1β: 46,5% increased) groups. Results support the existence of an inflammatory state mediated by an increased expression of TLR2 and pro-inflammatory cytokines IL-1β, IL-6 and TNF-α in T1DM